The feasibility of semi-automatically generated red bone marrow segmentations based on MR-only for patients with gynecologic cancer. Issue 1 (April 2017) - Andreychenko, Anna; Kroon, Petra S.; Maspero, Matteo; Jürgenliemk-Schulz, Ina; De Leeuw, Astrid A.C.; Lam, Marnix G.E.H.; Lagendijk, Jan J.W.; van den Berg, Cornelis A.T.
Abstract: Purpose: For patients with cervical cancer the delivery of chemotherapy with radiotherapy improves survival compared with radiotherapy alone. However, high rates of acute hematologic toxicity occur when combining both therapies due to the damage of the red bone marrow (RBM). This study aimed to reduce the radiation damage to the RBM. A tool has been developed for semi-automatic delineation of the red bone marrow based on MR-only. This delineation can be included into the treatment planning process to reduce the volume of RBM irradiated in patients receiving pelvic radiation therapy. Methods: 13 patients with cervical cancer were enrolled. All the patients underwent MR, CT and FDG-PET imaging. A tool for RBM determination from water and fat MR images was developed. Our MR-based RBM tool was optimized and validated with the FDG-PET scans of the patients. Results: Our tool identified RBM regions in the pelvic area. The mean total volume of these regions was 34% of the pelvic bone marrow. The corresponding SUV values based on the FDG-PET scans were above the reported threshold of active/red bone marrow. Conclusion: This study shows that delineations of the RBM for the radiotherapy with RBM sparing can be generated semi-automatically using MR scans only.